2015
DOI: 10.1513/annalsats.201412-559oc
|View full text |Cite
|
Sign up to set email alerts
|

Population-based Incidence of Pulmonary Nontuberculous Mycobacterial Disease in Oregon 2007 to 2012

Abstract: This is the first population-based estimate of pulmonary NTM disease incidence in a region within the United States. In Oregon, disease incidence rose slightly during 2007 to 2012, and although more common in female individuals overall, disease was more common among male individuals less than 60 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
100
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(115 citation statements)
references
References 19 publications
12
100
2
1
Order By: Relevance
“…Having incidence rates as well as estimates of the duration of infection allows more precise estimation of the future burden of NTM PD. The authors found an annual incidence rate of 1.1-1.5 per 100 000 population, similar to the average annual incidence estimated for Denmark of 1 per 100 000 population during 1997-2008 [8] but lower than the available average age-adjusted (to the US population) annual incidence of 3.8 per 100 000 from Oregon, USA [24]. However, case definitions in both the Danish and Oregon studies were based on American Thoracic Society microbiologic criteria, which are 50-73% more sensitive than ICD codes [13,15,25].…”
supporting
confidence: 72%
“…Having incidence rates as well as estimates of the duration of infection allows more precise estimation of the future burden of NTM PD. The authors found an annual incidence rate of 1.1-1.5 per 100 000 population, similar to the average annual incidence estimated for Denmark of 1 per 100 000 population during 1997-2008 [8] but lower than the available average age-adjusted (to the US population) annual incidence of 3.8 per 100 000 from Oregon, USA [24]. However, case definitions in both the Danish and Oregon studies were based on American Thoracic Society microbiologic criteria, which are 50-73% more sensitive than ICD codes [13,15,25].…”
supporting
confidence: 72%
“…To measure T and B cell frequency and proliferation, peripheral blood mononuclear cells (PBMC) and BAL cells were first stained with anti-CD4 (Tonbo Biosciences, San Diego, CA), CD8b (Beckman Coulter, Brea, CA), CD20 (BioLegend, San Diego, CA), IgD (Southern Biotech, Birmingham, AL), and CD27 (Tonbo Biosciences), then fixed and permeabilized before staining with anti-Ki67 (BD Pharmingen, San Diego, CA). To determine the frequency of MAC-specific T cells, 10 6 PBMC and BAL cells were stimulated with 10 ml MAC lysate, anti-CD3 (positive control), or media alone (negative control) for 16 hours in the presence of brefeldin A. Cells were stained with anti-CD4 and CD8b, then permeabilized and intracellularly stained with anti-IFNg, TNF-a, and macrophage inflammatory protein-1 beta (MIP1b) (15).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Although disseminated NTM disease is seen almost exclusively in immunosuppressed individuals, the vast majority of pulmonary NTM disease in the United States is due to Mycobacterium avium complex (MAC) and occurs in seemingly immunocompetent patients, disproportionately affecting females, older persons, and those with bronchiectasis or chronic obstructive lung disease (2)(3)(4)(5)(6)(7). Incidence rates are between 5/100,000 (general population) and 30/100,000 (.80 years old) patient-years, and are on the rise (6).…”
mentioning
confidence: 99%
“…NTM cause chronic, debilitating pulmonary disease primarily affecting HIV-negative people over age 45, as well as younger patients with cystic fibrosis (CF) [2, 5]. Approximately 55% of all cases occur in adults over age 65 [6, 7]. Pulmonary NTM disease disproportionately affects females and occurs more frequently in those with chronic underlying lung disease such as chronic obstructive pulmonary disease (COPD) and bronchiectasis [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found that the incidence and/or prevalence of NTM disease increased 2-6% per year [6, 8, 14]. This increase is even more dramatic at 8.7% per year from 1997 to 2007 in the Medicare population [15].…”
Section: Introductionmentioning
confidence: 99%